Prevalence, risk factors and health-seeking behavior of menstrual disorders among women in India: a review of two-decade evidence - Puja Das; Suresh Jungari (Global Health Action)
Background Menstrual health is critical for women of reproductive age. It is also evident that menstrual disorders have contributed to the increasing burden of non-communicable diseases. Objective To our knowledge, no literature review explicitly addresses the prevalence, risk factors, and health-seeking behaviour of menstrual disorders in India. Therefore, the current study aims to synthesize the available scientific evidence on the prevalence and risk factors of menstrual disorders in India over the last two decades. Methods We followed PRISMA guidelines to conduct the review. We used Google Scholar, PubMed, JSTOR, Scopus, and Sci Direct search engines to find eligible research studies and extracted data from 2000 to 2022. We also conducted quality appraisals of included studies in the review. Results Results show that the prevalence of any menstrual disorders ranges from 3% to 87%. Among all menstrual disorders, Dysmenorrhea was reported to be high (46% to 76%) among women, followed by premenstrual symptoms (PMS) (40% to 71%), while PCOS (3% to 14.14%) was less. The study further found that irregular lifestyle, obesity, inadequate diet, age at marriage, family history, smoking, and place of residence factors is associated with menstrual disorders in India. As far as health-seeking for menstrual disorders is concerned, one-third of women sought treatment for menstrual disorders. Conclusion The present study has revealed that most women reported high rates of Dysmenorrhea, while Polycystic Ovary Syndrome (PCOS) is less prevalent. The study findings suggest that health-seeking behaviour is the most important factor in reducing menstrual disorders, which has long-term effects of increasing other comorbidities.